Determinant Factors of Nurse Job Satisfaction in Hospital Ward - Dirgahayu Vega Amalia; Arief Yanto; Tri Hartiti; Vivi Yosafianti Pohan (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2023)
An unmanaged nurse performance satisfaction could reduce productivity, motivation, organisational commitment, and performance, increasing absenteeism and work turnover. Nurse performance satisfaction could be affected by needs, aspirations, allowance, behaviour, income, leadership style, job, workload, work environment, facility, leadership, promotion, work partner, supervisor, productivity, work efficacy, policy, and work condition. This study aims to determine the factors related to Inpatient Ward Nurse Performance Satisfaction at KRMT Wongsonegoro Hospital. It is an associative quantitative study using a cross-sectional approach. The research subject was an hospital ward nurse with criteria such as practitioner nurse with a diploma, bachelor's, or professional degree with a minimum of a year of working experience. One hundred forty-eight respondents were chosen using proportionate simple random sampling. The research focuses on measuring determinant factors that affect nurses' performance satisfaction using analysis of multiple linear regression tests with a backward method. The research finding shows the determinant variable of nurse performance satisfaction are nurse perception toward the leadership of the chief nurse (X1), nurse perception toward work (X2), and nurse perception toward workload (X3). The variables show significant positive relationships that simultaneously affect nurse performance satisfaction (Y) at 83.3%. The dominant variable that affects nurse performance satisfaction (Y) is nurse perception toward work (X2). It is because the knowledge owned by nurse make them happy and positively impact their responsibility. The unity between knowledge, feeling, and responsibility signifies accomplished nurse work satisfaction.